Transformation of religious consciousness in kazakh society (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the formation and development of the religious consciousness of society, changes in the religious circumstances, the issue of tolerance and mutual respect between religions was considered. The authors analyze the religions which past and the future, their cultural and historical importance are contiguous with the spiritual heritage of the Kazakh people. In addition, the article is based on common interests of Islam and its relation with other religions, their formation and development in the Kazakh land and also an analysis and conclusion was made. In each of the last level of superstition, it is comparable to analyze the changes in the religious consciousness of the people of Kazakhstan. Finally, religion is marked as a unifying factor in society, as well as regulatory acts regulating social behavior in natural value.Key words: religious consciousness, religious, interreligious harmony, religious, Islam, tengrianism.